The Essential Oil Composition of Tanacetum densum (Labill.) Heywood ssp eginense Heywood from Turkey - Polatoglu, Kaan; Demirci, Betul; Demirci, Fatih; Goren, Nezhun; Baser, Kemal Huesnue Can (ACG PUBLICATIONS, 2012)
Water-distilled essential oils from aerial parts of Tanacetum densum (L.) Heywood ssp. eginense Heywood, from Turkey was analysed by GC and GC-MS. T. densum ssp. eginense flower, stem and leaf oils were characterized with camphor (30.9%, 25.7%, 27.7%), 1,8-Cineole (12.4% flower oil), camphene (10.6%, %7.0, flower and leaf oils), bornyl acetate, (9.4%, 11.8%, stem and leaf oils), alpha-pinene (7.0%, %5.3, flower and leaf oils), borneol (5.1%, 5.2%, stem and leaf oils), neodihydrocarveol (5.1%, flower oil). An unidentified compound was also present in flower, stem and leaf oils (11.5%, 27.2%, 20.5%). A comparison is done with the previous investigations on the other subspecies of T. densum and the differences were investigated. Flower and stem oils did not show any significant activity to the tested microorganisms when compared to positive control chloramphenicol. Flower and stem oils both showed cytotoxicity to Vibrio fischeri.
Keywords: Tanacetum densum ssp eginense; Astereceae; Essential oil; antibacterial activity; Vibrio fischeri cytotoxic activity; camphor; 1,8-cineole; camphene; bornyl acetate; alpha-pinene; borneol; neodihydrocarveol; SUBSP AMANI; SESQUITERPENE LACTONES; SIVASICUM; Plant Sciences; Chemistry; Pharmacology & Pharmacy